Evaluation of rat kidney aldose reductase inhibitory activity of some N-acetyl dehydroalanine derivatives - Süzen, Sibel (My University, 2011)
Aldose reductase (AR) is an enzyme that catalyzes the conversion of glucose to sorbitol, which is in turn converted to fructose by sorbitol dehydrogenase. Increased AR activity has been implicated in the pathogenesis of diabetic complications such as neuropathy, nephropathy, retinopathy, and cataract. Inhibitors of AR thus seem to have the potential to prevent or treat diabetic complications. At present, however, side effects and/or insufficient pharmacokinetic profiles have made most of the drug candidates undesirable. In this study, the synthesis (l-o) and ARI activity of 15 N-acetyl dehydroalanine derivatives (a-o) are described. The synthesized compounds mainly contained aliphatic and aromatic side chains. The insertion of ethyl and chloro propyl side chains were shown to be more effective than the rest of the compounds. Between the synthesized compounds N-ethyl (b) and N-propylchloride (h) derivatives showed the best ARI activities. © 2011 Springer Science+Business Media, LLC.
Keywords: Aldose reductase; Dehydroalanine; Inhibition; Polyol pathway; Synthesis